2004
DOI: 10.1046/j.1471-4159.2004.02284.x
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone amplifies excitotoxic damage of cultured oligodendrocytes

Abstract: An overactivation of a-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA)/kainate receptors has been implicated in the pathophysiology of oligodendrocyte damage in demyelinating disorders of the CNS. We decided to examine the effect of testosterone on excitotoxic death of oligodendrocytes because a gender difference exists in the incidence and disease course of multiple sclerosis. Short-term pure cultures of oligodendrocytes (4 days in vitro) were exposed to a brief pulse with kainate or AMPA + cyclothiazid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…These results indicate that testosterone metabolites are valuable candidates for the treatment of diabetic neuropathic pain, at least in male individuals. However, since androgens may have adverse effects, including the induction of neuronal apoptosis (Yang et al 2002, Caruso et al 2004, Estrada et al 2006, Gatson & Singh 2007, further studies are necessary to exclude undesirable effects of the treatments before envisaging a possible clinical application of the present findings.…”
Section: Discussionmentioning
confidence: 94%
“…These results indicate that testosterone metabolites are valuable candidates for the treatment of diabetic neuropathic pain, at least in male individuals. However, since androgens may have adverse effects, including the induction of neuronal apoptosis (Yang et al 2002, Caruso et al 2004, Estrada et al 2006, Gatson & Singh 2007, further studies are necessary to exclude undesirable effects of the treatments before envisaging a possible clinical application of the present findings.…”
Section: Discussionmentioning
confidence: 94%
“…For example, T was shown to exacerbate the size of a lesion resulting from middle cerebral artery occlusion in male rats [166; 167]. Furthermore, T treatment increased kainic acid-induced cell death of cultured oligodendrocytes [168]. Thus, androgens can be protective or damage promoting, but the mechanism underlying this duality is still unclear.…”
Section: Neuroprotective Verses Neuroendangering -Genomic Verses Nongmentioning
confidence: 99%
“…Alternatively, other data show that testosterone can induce cell death. For example, superphysiological levels of testosterone have been shown to induce neuronal and glial cell death and to amplify excitotoxicity in vitro (Caruso et al, 2004;Gatson and Singh, 2007;Orlando et al, 2007). Furthermore, colleagues (2002, 2005) have demonstrated that chronic testosterone replacement increased lesion volume in a middle cerebral artery occlusion model in male rats, and that gonadectomy or administration of 17b-estradiol reduced lesion volume, which suggests that testosterone may be deleterious in CNS injury.…”
mentioning
confidence: 99%